Pengembangan Seedian Emulgel Kombinasi Fraksi Aktif Daun Kersen dan Kulit Kayu Manis Untuk Ulkus Diabetikum - Brigita Julianti Manalu; Novitaria Br Sembiring; Astriani Natalia Br Ginting (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Introduction: Diabetic ulcer is a serious complication of diabetes mellitus that is often accompanied by bacterial infections, necessitating effective topical therapy. Kersen leaves (Muntingia calabura L.) and cinnamon bark (Cinnamomum sp.) are known to contain bioactive compounds with antibacterial potential. Aim: This study aims to develop and evaluate the antibacterial activity of an emulgel formulation containing a combination of active fractions from kersen leaves and cinnamon bark as a candidate for topical therapy for diabetic ulcers. Method: The active fractions were obtained through extraction and fractionation processes, then formulated into an emulgel at varying concentrations of 10%, 30%, 50%, 60%, and 70%. Antibacterial activity was tested against Staphylococcus aureus using the agar disk diffusion method, with clindamycin as a positive control and the emulgel base as a negative control. Result: The results showed that the emulgel began to exhibit antibacterial activity at a concentration of 50%, with an average inhibition zone diameter of 12.96 mm. Increasing the concentration to 60% and 70% enhanced the inhibition zones to 14.00 mm and 15.24 mm, respectively. Clindamycin produced an inhibition zone of 29.57 mm, while the negative control showed no inhibitory activity. Conclusion: The emulgel combination of active fractions from kersen leaves and cinnamon bark possesses concentration-dependent antibacterial activity and has the potential to be developed as a topical herbal preparation to support diabetic ulcer therapy.